RELATIONSHIP BETWEEN LOW BIRTH WEIGHT AND INFECTIOUS DISEASES WITH STUNTING IN CHILDREN AGED 4 TO 5 YEARS - Nur Linawati (Indonesian Journal of Multidisciplinary Science, 2022)
Stunting is a nutritional problem that has a high prevalence in Indonesia. Stunting is directly affected by birth weight and infectious diseases. This study aims to analyze the relationship between low birth weight and infectious diseases with the incidence of stunting in children under two. This type of research uses a case-control design. Sampling was done by purposive sampling technique. The sample size is 105 children (35 stunted children and 70 non-stunting children). In collecting data, researchers used instruments in the form of questionnaires, interviews and height measurement tools. Questionnaires are used to determine birth weight which has been tested for validity and reliability. The collection of data on infectious diseases of children was carried out by structured interviews with the children's parents and medical records from the puskesmas doctors. Then the height measurement tool used is a stature meter SH - 2° with an accuracy of 0.1. To determine stunting using the z-score using the NCHS standard value. The results of this study on the birth weight variable obtained the RE (Risk Estimtae) value of 7.667 (95% CI: 3.718 - 15.807). Then the infectious disease variable obtained RE (Risk Estimate) value of 0.521 (95% CI: 0.418 – 0.649). The conclusion of this study is that there is a relationship between low birth weight and infectious diseases with the incidence of stunting in children aged 4 to 5 years.